Neurologic Complications of Smallpox Vaccination - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
Smallpox and smallpox vaccination is reviewed from the Departments of Neurology, Yale University School of Medicine, New Haven, CT, and University of New Mexico School of Medicine, Albuquerque.